Influence of different sized nanoparticles combined with ultrasound on the optical properties of in vitro knee joint and knee osteoarthritis cartilage tissue was studied by OCT and diffuse reflectance spectroscopy. (17th November 2021) - An, Ran; Wei, Huajiang; Zhuang, Ze; Guo, Zhouyi; He, Yonghong; Xie, Shusen; Yang, Hongqin; Gu, Huaimin
Abstract: The penetration and accumulation of zinc oxide nanoparticles (ZnO NPs) with different sizes in human normal knee joint (NKJ) tissue and knee osteoarthritis (OA) tissue were studied by continuous optical coherence tomography and diffuse reflectance (DR) spectroscopy in this paper, and the effects of ZnO NPs of two sizes (30 nm and 90 nm) and ultrasound (US) on the optical properties of human NKJ and OA tissue were evaluated. The results show that the average attenuation coefficients of NKJ tissue decrease by 14.90%, 26.91%, 33.52% and 37.01%, and the DR spectra increases by 8.444%, 12.901%, 18.219% and 26.125%, respectively, after being treated with 90 nm ZnO NPs, 90 nm ZnO NPs/US, 30 nm ZnO NPs and 30 nm ZnO NPs/US. The average attenuation coefficients of OA tissue are reduced by 32.14%, 49.51%, 57.85% and 72.30%, and the DR spectra increase by 17.426%, 23.116%, 25.218% and 29.326%, respectively, after being treated with 90 nm ZnO NPs, 90 nm ZnO NPs/US, 30 nm ZnO NPs and 30 nm ZnO NPs/US. It is concluded that the optical properties of NKJ and OA tissues are greatly influenced by ZnO NPs and US. Nanoparticles have a greater impact on OA tissue than on NKJ tissue.